Developing Accelerator Mass Spectrometry Capabilities for Anthropogenic Radionuclide Analysis to Extend the Set of Oceanographic Tracers - Hain, Karin; Martschini, Martin; Gülce, Fadime; Honda, Maki; Lachner, Johannes; Kern, Michael; Pitters, Johanna; Quinto, Francesca; Sakaguchi, Aya; Steier, Peter; Wiederin, Andreas; Wieser, Alexander; et al. (Frontiers in Marine Science, 2022)
Recent major advances in Accelerator Mass Spectrometry (AMS) at the Vienna Environmental Research Accelerator (VERA) regarding detection efficiency and isobar suppression have opened possibilities for the analysis of additional long-lived radionuclides at ultra-low environmental concentrations. These radionuclides, including 233U, 135Cs, 99Tc, and 90Sr, will become important for oceanographic tracer application due to their generally conservative behavior in ocean water. In particular, the isotope ratios 233U/236U and 137Cs/135Cs have proven to be powerful fingerprints for emission source identification as they are not affected by elemental fractionation. Improved detection efficiencies allowed us to analyze all major long-lived actinides, i.e., 236U, 237Np, 239,240Pu, 241Am as well as the very rare 233U, in the same 10 L water samples of a depth profile from the northwest Pacific Ocean. For this purpose, a simplified and very flexible chemical purification procedure based on extraction chromatography (a single UTEVA® column) was implemented which can be extended by a DGA® column for Am purification. The procedure was validated with the reference materials IAEA-381/385. With the additional increase in ionization efficiency expected for the extraction of actinides as fluoride molecules from the AMS ion source, a further reduction of chemical processing may become possible. This method was successfully applied to an exemplary set of air filter samples. In order to determine the quantitative 237Np concentration reliably, a 236Np spike material is being developed in collaboration with the University of Tsukuba, Japan. Ion-Laser Interaction Mass Spectrometry (ILIAMS), a novel technique for the efficient suppression of stable isobaric background, has been developed at VERA and provides unprecedented detection sensitivity for the fission fragments 135Cs, 99Tc, and 90Sr. The corresponding setup is fully operational now and the isobar suppression factors of >105 achieved, in principle, allow for the detection of the mentioned radionuclides in the environment. Especially for 90Sr analysis, this new approach has already been validated for selected reference materials (e.g., IAEA-A-12) and is ready for application in oceanographic studies. We estimate that a sample volume of only (1–3) L ocean water is sufficient for 90Sr as well as for 135Cs analysis, respectively.